Teachers’ Beliefs of Culture in Intercultural Language Learning: A study in North Maluku - Husain, Balqis; Rd. Safrina; Gandana, Isti Siti Saleha (STAIN Majene, 2025)
This study investigates EFL teachers' conceptualizations of culture and intercultural language learning (ILL) and examines how cultural values are reproduced in classroom practices. This research was conducted as a qualitative single-case exploratory study involving two senior high school EFL teachers from North Maluku, Indonesia, selected through purposive sampling. Data were collected through semi-structured interviews and document analysis, and analyzed thematically. The findings reveal distinct differences in how the teachers conceptualize culture and implement ILL. One teacher adopts a reflective and critical approach aligned with Byram's concept of critical cultural awareness, emphasizing integrating local culture and small 'c' culture through experiential learning. This approach reflects a dynamic view of culture (culture as verb) and actively seeks to balance the influence of target cultures with local values. In contrast, the other teacher views culture as static (culture as noun), focusing on Big' C' culture and pragmatic linguistic access, relying heavily on digital resources without direct intercultural experiences. Reflections in this approach remain cognitive and affective but are not fully translated into pedagogical practice. These findings demonstrate how personal experience, access to learning resources, and pedagogical orientation shape teachers' beliefs and practices. The study underscores the need for professional development programs to strengthen teachers' critical cultural awareness and contextually relevant intercultural practices, while also highlighting the importance of equitable access to intercultural learning opportunities to reduce overreliance on digital or conventional materials.